Catastrophic health expenditure and the risk of depression among middle-aged and old people in China: a national population-based longitudinal study - Yaping Wang; Min Liu; Jue Liu (Cambridge University Press, 2023)
Abstract Aims To estimate the association of catastrophic health expenditure (CHE) with the risk of depression in middle-aged and old people in China. Methods We used data of 2011, 2013, 2015 and 2018 from the China Health and Retirement Longitudinal Study, which covered 150 counties of 28 provinces in China. CHE was calculated as out-of-pocket health expenditure exceeding 40% of a household's capacity to pay. Depression was measured by a 10-item Centre for Epidemiological Studies Depression Scale. We evaluated CHE prevalence and applied Cox proportional hazard models to estimate adjusted hazard ratios (aHRs) and 95% confident intervals (CIs) for the risk of depression among participants with CHE after controlling potential confounders, compared with those without CHE. Results Among 5765 households included in this study, CHE prevalence at baseline was 19.24%. The depression incidence of participants with CHE (8.00 per 1000 person-month) was higher than that of those without CHE (6.81 per 1000 person-month). After controlling confounders, participants with CHE had a 13% higher risk (aHR = 1.13, 95% CI: 1.02-1.26) of depression than those without CHE. In subgroup analysis, the association of CHE with depression was significant in males and in people with chronic diseases, of younger age, living in rural areas and of lowest family economic level (all P < 0.05). Conclusions Nearly one of five middle-aged and old people in China incurred CHE, and CHE was associated with the risk of depression. Concerted efforts should be made to monitor CHE and related depression episode. Moreover, timely interventions about CHE and depression need to be implemented and strengthened among middle-aged and old people.